LGBT+ Experiences of Custody: Gender Non-Conformity in Overtly Gendered Social Spaces - McMillan, Scott (University of Dundee, 2021)
LGBT+ people are evidenced globally as being negatively impacted by the criminal justice system and face specific challenges within custodial settings due to their sexual orientation or gender identity, in what are inherently heteronormative and overtly masculine spaces culturally, and where hard lines between sex and gender are actively enforced and even reified in policy and practice at the institutional level.

This dissertation sought to explore the experience of LGBT+ people in UK prisons relative to this hyper normatively gendered culture, and particularly masculinity, given that upwards of 90% of all people in custody are male. In so doing, it also sought to make recommendations for best practice based on these experiences.

A review of relevant policy regarding LGBT+ Human rights legislation and specifically in custodial settings in the UK and the US, and of current and historical understandings of masculinity in the West, was followed by thematic analysis of LGBT+ participant interviews, utilising the theoretical concepts and perspectives of Pierre Bourdieu to explore the social dynamics, embodied states and adaptive capitals of gender, sexuality, class and prisoner versus institutional cultures in custodial settings.

The data sample was taken from the AHRC-funded international project exploring experiences of LGBT+ prisoners in the UK of which this programme was part. The sample consisted of thirty interviews with LGBT+ prisoners, and 9 staff interviews, consisting of 5 individual interviews with managers and focus groups with 21 frontline staff.

Among the findings it was revealed gendered norms were codified in overly simple and stereotyped ways that arguably exacerbated the harms associated with these constructions. Variance of abuse versus acceptance; threat from peers versus threat from establishment; the nature of the threat posed and from whom; deployment of blanket policies; and agency, advocacy, and engagement with the system regarding LGBT+ issues, were dependent on specific custodial environments relative to sex [male or female], offence type [sex offenders or mainstream] and social class [lower/working or middle/upper]. Male mainstream environments were the most hypermasculine and overtly hostile to LGBT+ people in custody with the primary threat coming from peers in the forms of verbal and physical abuse. Male sex offender and female environments were more accepting of LGBT+ and were overrepresented in numbers, with the primary threat coming from the establishment in the form of policies and practice to both police open, and overlook clandestine, same sex activity on the grounds of female vulnerability and predatory male sexuality, respectively. Staff reported lack of training, education, and ambivalence to the sensitivities of gender identity and sexual orientation in the face of maintaining safety and security, and scepticism of disingenuous actors manipulating transgender policies to gain access to female environments. Trans people in custody were the most visible, contentious and discussed issue from an institutional perspective, constructed as simultaneously vulnerable and risky, and experienced negative treatment and prejudice regardless of differing prison environments.

This dissertation concluded that current policies to both police or ignore, were tantamount to incentivised homophobia and institutional thoughtlessness, and should be replaced with a system of sanctioned mediation, along with the introduction of additional frontline staff, and regular mandatory training on diversity issues and mental health and wellbeing. Furthermore, a review of current academic, political, cultural, and institutional discourse on gender and its codification in policy and practice was deemed necessary to transcend, rather than entrench, gendered stereotypes. Doing so would benefit not just those gender non-conforming/non-binary people in custody – particularly trans people in custody who embody both extremes in this context – but the majority of heterosexual men and women in custody for whom these extreme positions are operationalised around, and who come to internalise and are governed by them, despite being embodied by a minority within these populations.